Exploring Pre-Service Teachers' Knowledge and Perceptions of Classroom Assessment: A Pathway to Enhanced Pedagogy - Joaquin, Cleo Jude A. (Future Science / FSH-PH Publications, 2024)
This present study investigates the extent to which pre-service teachers understand classroom assessment and their conceptions of its effects on student learning and improvement of instruction. In the survey response of 106 pre-service teachers, the knowledge in assessment procedures was strongly positive. However, there is room for development in areas such as planning for varied learners, data interpretation, and feedback (average mean = 3.74). The mean score of 4.00 reveals that pre-service teachers consider assessment important for identifying students' strengths, and fine-tuning education, but targeted training in real skills is recommendable for delivering assessment effectively at an educational institution.